Incorporation of a 3D-printed feline larynx model as a teaching tool for veterinary students - Sakai, Daniel M. (2021)
Endotracheal intubation (EI) in cats is associated with risk of mortality (Brodbelt et al., 2007). Thiscan be decreased with simulation-based training. We evaluated the implementation of a low-costfeline larynx model (LaryngoCUBE 2019) as a training device for veterinary students.The students received either standard training (ST, n = 22) or trained with a larynx model the dayprior to anesthesia (MT, n = 16). Veterinary students practiced EI in cats sedated withdexmedetomidine and hydromorphone and anesthetized with propofol. They attempted EI andevaluated the difficulty with a visual analogue score (VAS; 0 cm = very easy and 10 cm = extremelydifficult). Up to three attempts were permitted. For successful EI, we measured the time andnumber of attempts. Fisher?s exact and Mann-Whitney tests compared groups with alpha at 5%.The VAS [median (minimum ? maximum)] on the ST and MT were 4.5 (0.0 ? 10.0) cm and 3.0 (0.2 ?10.0) cm, respectively (p = 0.029). The failure rate was 27% on the ST and 25% on the MT (p = 1.000).The EI time on ST [58 (18 ? 160) seconds] was longer, but not statistically different from MT [29 (13 ?120) seconds; p = 0.101]. The number of attempts on ST [2 (1 ? 3)] was higher than MT [1 (1 ? 3), p =0.005)].Students that practiced with a larynx model found that EI was easier, took less attempts for EI, andtended to be faster. However, EI success rate in MT was not improved.ReferencesBrodbelt, D. C. et al. (2007) Risk factors for anaesthetic-related death in cats: results from theconfidential enquiry into perioperative small animal fatalities (CEPSAF). Br J Anaesth, 99:617?23.LaryngoCUBE 2019, Hospital Escuela De Pequeños Animales website, viewed 9 December 2019.